Skin cancer in children after organ transplantation - Imko-Walczuk, Beata; Roskosz-Stożkowska, Magdalena; Szymańska, Katarzyna; Kadylak, Damian; Dębska-Ślizień, Alicja (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Skin cancer is the second most common complication of organ transplantation in children. The frequency of skin cancer incidence after organ transplantation is different in paediatric and adult populations. The post-transplant lymphoproliferative disease is the most common group of malignancies after organ transplantation in paediatric population. The majority of researchers who examined children with kidney, liver, heart or lungs grafts observed that the risk of skin cancer was three times higher than in the general population whereas in adults even 200 times higher. The occurrence of skin cancer in children after transplantation is extremely rare during childhood. The risk increases in early adulthood. Malignancies occurring after solid organ transplantation result from many different factors. These include the immunological condition of the child, dose and time of immunosuppression, and oncogenic viruses. The increased risk of skin cancer following paediatric transplantation requires prevention and adequate education of children and their parents. These involve avoiding sun exposure and protection such as sunscreens and protective clothing. The early detection of cancer in transplant recipients is very important. Prevention of cancer includes regular dermatological examination.